IMPLANT-SUPPORTED PROSTHETICS AND ADAPTATION CHALLENGES: COMPARATIVE ANALYSIS OF IMMEDIATE AND DELAYED LOADING PROTOCOLS AND PREVENTION OF PERI-IMPLANT COMPLICATIONS - Shovkatov, O; Sharipov, S; Akhundjanov, A (Uzbekistan Open Conference, 2025)
Implant-supported prosthetics represent a cornerstone in the management of edentulous patients, ensuring functional restoration, esthetics, and improved quality of life. However, adaptation challenges remain, particularly regarding the choice of loading protocols and prevention of peri-implant complications. This prospective multicenter study evaluates the clinical and biological outcomes of immediate versus delayed loading of dental implants, with a focus on peri-implant tissue health, patient adaptation, and long-term stability.A total of 80 patients were recruited and divided into two groups based on loading protocols. Clinical parameters included implant survival, peri-implant tissue indices, masticatory efficiency, and patient satisfaction. Statistical analysis revealed that while both protocols achieved high survival rates (>95%), immediate loading resulted in faster adaptation and greater patient satisfaction but showed a slightly higher incidence of peri-implant mucositis and peri-implantitis. Preventive strategies such as strict oral hygiene, regular follow-up, and use of bioactive implant surfaces were found to be essential in minimizing complications.
Keywords: implant-supported prosthetics; immediate loading; delayed loading; peri-implantitis; peri-implant complications; patient adaptation